Biogenesis of Cytoplasmic Membranous Vesicles for Plant Potyvirus Replication Occurs at Endoplasmic Reticulum Exit Sites in a COPI- and COPII-Dependent Manner - Wei, Taiyun (American Society for Microbiology (ASM), 2008)
Single-stranded positive-sense RNA viruses induce the biogenesis of cytoplasmic membranous vesicles, where viral replication takes place. However, the mechanism underlying this characteristic vesicular proliferation remains poorly understood. Previously, a 6-kDa potyvirus membrane protein (6K) was shown to interact with the endoplasmic reticulum (ER) and to induce the formation of the membranous vesicles. In this study, the involvement of the early secretory pathway in the formation of the 6K-induced vesicles was investigated in planta. By means of live-cell imaging, it was found that the 6K protein was predominantly colocalized with Sar1, Sec23, and Sec24, which are known markers of ER exit sites (ERES). The localization of 6K at ERES was prevented by the coexpression of a dominant-negative mutant of Sar1 that disables the COPII activity or by the coexpression of a mutant of Arf1 that disrupts the COPI complex. The secretion of a soluble secretory marker targeting the apoplast was arrested at the level of the ER in cells overexpressing 6K or infected by a potyvirus. This blockage of protein trafficking out of the ER by 6K and the distribution of 6K toward the ERES may account for the aggregation of the 6K-bound vesicles. Finally, virus infection was reduced when the accumulation of 6K at ERES was inhibited by impairing either the COPI or COPII complex. Taken together, these results imply that the cellular COPI and COPII coating machineries are involved in the biogenesis of the potyvirus 6K vesicles at the ERES for viral-genome replication.